2000
DOI: 10.1149/1.1393409
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of H[sub 2] and CO in a H[sub 2]-H[sub 2]O-CO-CO[sub 2] System at the Interface of a Ni-YSZ Cermet Electrode and YSZ Electrolyte

Abstract: The electrochemical oxidation of H2 and CO in a H2‐H2O‐CO‐CO2 system at the interface of a porous Ni‐yttria stabilized zirconia (YSZ) cermet electrode and YSZ electrolyte has been studied using complex‐impedance spectroscopy and direct‐current polarization measurements of 1023 and 1273 K under a constant oxygen partial pressure. The polarization resistance increased when the CO concentration ratio. pCO/false[pH2+pCOfalse] , exceeded 0.2 and 0.5 at 1023 and 1273 K, respectively. The electrochemical oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(127 citation statements)
references
References 8 publications
9
118
0
Order By: Relevance
“…Therefore, the lowest frequency peak (<1 Hz) could be attributed to CO conversion, by analogy to the analysis of the (dry-humid) case. This peak being at a lower frequency compared to the H 2 conversion peak (2 Hz) is consistent with the fact that electrochemical conversion of CO on Ni-YSZ is known to be slower than that of H 2 [25,26]. Furthermore, this low-frequency peak is negligible at 710°C and becomes significant only above 760°C, indicating that CO is only scarcely electrochemically converted at 710°C.…”
Section: Comparison Of Performance With Dry and Humid Mixtures: Effecsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the lowest frequency peak (<1 Hz) could be attributed to CO conversion, by analogy to the analysis of the (dry-humid) case. This peak being at a lower frequency compared to the H 2 conversion peak (2 Hz) is consistent with the fact that electrochemical conversion of CO on Ni-YSZ is known to be slower than that of H 2 [25,26]. Furthermore, this low-frequency peak is negligible at 710°C and becomes significant only above 760°C, indicating that CO is only scarcely electrochemically converted at 710°C.…”
Section: Comparison Of Performance With Dry and Humid Mixtures: Effecsupporting
confidence: 82%
“…Matsuzaki and co-workers have shown that, in H 2 /CO mixtures, the water-gas shift reaction plays an important role because it is much faster than the oxidation reactions [26]. Therefore, the intermediate peaks could be related to the additional H 2 production through the water-gas shift reaction.…”
Section: Comparison Of Performance With Dry and Humid Mixtures: Effecmentioning
confidence: 99%
“…These assumptions can be compared to the result from Matsuzaki and Yasuda in [47], where it was concluded that the electrochemical oxidation rate of H 2 at the interface in a porous…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
“…Carbon monoxide can be oxidized in the electrochemical reaction, but also reacts with water in the WGSR [48]]. Note that the WGSR is in general much faster than the carbon monoxide electrode reaction [47][48][49]. Methane reacts with steam in the MSR.…”
Section: Internal Reforming Reactionsmentioning
confidence: 99%
“…Similarly, impedance spectroscopy was used to examine the effect of carbon monoxide concentration, where it was identified that increasing CO produced increased carbon deposition with the exception of the cell being operated on pure carbon monoxide, implying that the mechanism of carbon formation is via a hydrogen assisted CO dissociation route (Alzate-Restrepo 2010). Matsuzaki and Yasuda also identified an increased 20 polarisation resistance with increased carbon monoxide concentration, however the lower rate of chemical oxidation was attributed to a larger diffusion resistance of carbon monoxide compared to hydrogen (Matsuzaki 2000). This paper examines the effects of H 2 :CO ratios in syngas on a commercially available scandia doped 25 zirconia electrolyte utilising a nickel anode.…”
mentioning
confidence: 99%